2000
DOI: 10.1289/ehp.0010845
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality and reproductive endocrine function in relation to biomarkers of lead, cadmium, zinc, and copper in men.

Abstract: Blood lead (BPb), activity of delta-aminolevulinic acid dehydratase (ALAD), erythrocyte protoporphyrin (EP), blood cadmium (BCd), serum zinc (SZn), seminal fluid zinc (SfZn), serum copper (SCu), and parameters of semen quality and of reproductive endocrine function were measured in 149 healthy male industrial workers 20-43 years of age. The group contained 98 subjects with slight to moderate occupational exposure to Pb and 51 reference subjects. All of the subjects lived in Zagreb, Croatia. Significant (p < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
162
1
11

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(188 citation statements)
references
References 48 publications
14
162
1
11
Order By: Relevance
“…In addition, they observed lower motility (<50%) and morphology (<14%), with >35 μg/dL in whole blood. Telisman and colleagues also showed that high lead concentration in blood significantly lowers sperm density and motility (36.7 μg/dL) [75]. High concentrations of lead seem to be clearly associated with sperm damage.…”
Section: Heavy Metalsmentioning
confidence: 94%
“…In addition, they observed lower motility (<50%) and morphology (<14%), with >35 μg/dL in whole blood. Telisman and colleagues also showed that high lead concentration in blood significantly lowers sperm density and motility (36.7 μg/dL) [75]. High concentrations of lead seem to be clearly associated with sperm damage.…”
Section: Heavy Metalsmentioning
confidence: 94%
“…Other reports have shown a significantly negative correlation between blood lead concentration and semen quality [28,[70][71][72]. Benoff et al [70] determined the relationships between seminal lead levels and acrosome status and artificial insemination cycle fecundity (AI f) in semen donors.…”
Section: Metalsmentioning
confidence: 99%
“…Lead exposure is associated with neurologic (3-6), growth (3,7), and reproductive defects (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Lead exposure in men has been associated with abnormalities of spermatogenesis (9,(11)(12)(13)).…”
mentioning
confidence: 99%
“…Lead exposure in men has been associated with abnormalities of spermatogenesis (9,(11)(12)(13)). An inverse relationship between blood lead and sperm concentration has been reported (14,15). Animal studies tend to support the conclusion that lead exposure disrupts the reproductive hormones, but clinical studies evaluating the relationship between lead exposure and reproductive hormone changes are inconclusive (8,11).…”
mentioning
confidence: 99%